Estimating Aggregate Consumption Function in Indonesia: An Error Correction Approach - Panji Kusumo Prasetyanto; Jihad Lukis Panjawa; Jalu Aji Prakoso; Suci Nasehati Sunaningsih; Deni Ramdani (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
The aggregate consumption pattern in Indonesia tends to be volatile due to economic, social, political instability, and disasters affecting consumption expenditure and social welfare. Relooking at public expenditure and its determinant with the 1992-2019 time series is the focus of current research. This review aims to find out the change of aggregate consumption in Indonesia with the Life-Cycle Hypothesis. The method used to authenticate the research was the Direct Error Correction Model. Using this approach, short- and long-term consumption estimation will be found that is useful to stakeholders. The result of the test shows there is a relationship between determinants and aggregate consumption in Indonesia in both the short and the long terms. In short term, inflation affects the change of aggregate consumption, while in the long term, GDP, interest rate, and inflation affect consumption. Estimation building on hypothesis testing is useful to policymakers, particularly for macro-credential adjustment.